Influence of mental fatigue on physical performance, and physiological and perceptual responses of judokas submitted to the special judo fitness test - Campos, B. T.; Penna, E. M.; Rodrigues, J. G.; Mendes, T. T.; Maia-Lima, A.; Nakamura, F. Y.; Vieira, E. L. M.; Wanner, S. P.; Prado, L. S. (The Journal of Strength and Conditioning Research, 2022)
Mentally fatigued athletes present impaired aerobic performance, strength endurance, and manual dexterity, despite no changes in anaerobic performance and maximal muscle strength and power. Noteworthy, the effect of mental fatigue on physical performance during high-intensity intermittent tests that require specific motor skills of fighting sports has not been investigated. Therefore, this study aimed to verify whether mental fatigue influences performance and physiological and perceptual responses of judokas subjected to a high-intensity intermittent test designed specifically and validated for judo. Each judoka performed 2 experimental trials—a control trial one and the other one after the induction of mental fatigue. These trials were scheduled in a random and balanced order. In both trials, lactate, glucose, and cortisol concentrations, the heart rate variability, and perceptual variables were collected after the initial treatment and after the Special Judo Fitness Test (SJFT). The initial treatment consisted of a 30-minute cognitive demanding task (Stroop Color test) or watching a movie (control) and was followed by the SJFT. The Stroop Color test increased the perceptions of mental fatigue and effort, without affecting motivation for subsequent testing. Unexpectedly, mentally fatigued athletes did not show reduced performance during the SJFT. Regarding the physiological variables, no significant differences were identified between the 2 experimental conditions. We conclude that physical performance measured during a specific test for judokas is not impaired by a previous 30-minute cognitive task that causes mental fatigue. In addition, this cognitive task did not influence the physiological changes induced by the specific physical test.